ANALISIS PENYEBAB DAN DAMPAK PERCERAIAN DI KABUPATEN WONOGIRI PROVINSI JAWA TENGAH - Hutasoit, Imelda; Gandhi, Wali Mahendra; Simanullang, Welly Pratama; Huka, Adrianus Louse; Maromon, Yansen Alther (Institut Pemerintahan Dalam Negeri, 2024)
Family resilience is a very important aspect in supporting development, but changes in habits and social values ​​make the divorce rate higher, which has various negative impacts, especially on the lives of children. The aim of this research is to describe and analyze the picture of divorce, the causes and impacts of divorce in Wonogiri Regency. The research method used is descriptive qualitative. Data collection techniques used interviews and documentation. The data analysis technique uses several stages, namely preparing the data, reading all the data, presenting the data, coding or organizing the data, analyzing the data, describing the data that has been analyzed, and interpreting the data or drawing conclusions. The research results illustrate that divorce cases fluctuate, but the number is very high. Complaint divorce or divorce at the wife's request is the highest and shows more than three times the number compared to talak divorce or divorce at the husband's request. The causes of divorce include problems in family communication, economic problems, feelings of jealousy, feelings of superiority, infidelity, domestic violence (KDRT) and the rise of early marriage. Regarding the impact, divorce in Wonogiri Regency has an impact on various parties, namely children, divorced couples and extended families. Efforts to overcome divorce can be carried out by providing outreach to teenagers to avoid promiscuity, providing pre-marital education so that they can maintain the integrity of the household, and by improving the quality of human resources officers so that reporting cases of violence can be done quickly and accurately.